PENGGUNAAN MEDIA SOSIAL DAN KEMARAHAN RELIGIUS DALAM KASUS PEMBAKARAN VIHARA DI KOTA TANJUNG BALAI, INDONESIA - Syahputra, Iswandi (IAIN Tulungagung, 2018)
Public activities carried out on social media may trigger religious identity based social riot. Such social unrest is observed to have surfaced initially as religious rage channeled via social media. It is, indeed, a fact that various issues on religion, which is regarded as sacred, hallowed, and revered, are discussed freely on social media, and it may very easily incite social turbulence. In the case of vihara burning and rioting in the city of Tanjung Balai, North Sumatera, Indonesia, a social riot was instigated by users of social media who mutually provoked resentment against one another, there was also the Budha statue which posed as a latent triggering factor threatening inter-religious relations within societal culture fond of congregating. This article discusses the case of vihara burning which had occurred in Tanjung Balai, North Sumatera, Indonesia, where in research data were acquired through in-depth interviews with several informants active on social media, community figures, and police personnel.